Advanced materials for lithium rechargeable battery - Nurul Hayati Idris (University of Wollongong (Degree of Doctor of Philosophy), 2012)
Due to the rapid increase in the use of portable computers, mobile phones, and electric vehicles, there is an increasing demand for larger capacity, smaller size, lighter weight and lower priced rechargeable batteries. Lithium ion battery technology offers the highest energy densities by weight of all the commercial rechargeable battery technologies, with high voltage, long cycle life, and a wide environmental operation range.